Deforestation of Tropical Rainforests: Economic Causes and Impact on Development - Torsten Amelung; Markus Diehl (Institut für Weltwirtschaft, J.C.B Mohr (Paul Siebeck); ZBW - Leibniz Information Centre for Economics, 1992)
The book reveals an analysis of the sources of deforestation in tropical countries. In the first part, the authors provide data on the forest resources that have been depleted as a result of activities of different industries or their supply chain partners. In the second part of the book, there is an evaluation to which extent these economic activities contribute to the development of the respective tropical countries. The data derived from these analyses might be helpful in pointing towards international solutions to reduce the deforestation in these countries.
Additional information: The study that lead to the publishing of this book was commissioned and finaced by Greenpeace e.V. in Hamburg.The valuable input of Heinrich Seul and other members of the Greenpeace staff are gratefully acknowledged.
Keywords: Q32; Q34; Q51; Q56; 330; Root causes of deforestation; Economic exploitation of tropical forests; Impact on domestic development